The impact of mind–body exercise on female breast cancer patients—a systematic review and meta-analysis of randomized controlled trials - Li, Lei; He, Yuanhada; Yang, Xiaojuan; Liu, Yang (Frontiers in Public Health, 2025)
ObjectiveTo evaluate the effects of mind–body exercise on breast cancer patients.MethodsA systematic search was conducted in the Cochrane Library, Embase, PubMed, Ovid, and Web of Science databases from inception to October 23, 2024, for randomized controlled trials (RCTs) assessing the effects of mind–body exercise on breast cancer patients. Inclusion criteria were: intervention group receiving mind–body exercises such as mindfulness or yoga; control group receiving standard care; participants aged ≥18 years with breast cancer; and outcomes including anxiety, fear of cancer recurrence (FCR), fatigue, IL-6, and 7 other indicators. Two reviewers independently screened the literature and extracted data. After assessing the methodological quality of the included studies using the Cochrane Risk of Bias tool, meta-analysis was conducted using RevMan 5.4 and Stata 15.0 software.ResultsA total of 47 RCTs involving 4,537 breast cancer patients were included. Meta-analysis results showed that compared to standard care, mind–body exercise significantly improved anxiety (SMD = −0.50, 95% CI [−0.73, −0.27], p < 0.0001), depression (SMD = −0.43, 95% CI [−0.60, −0.26], p < 0.00001), insomnia (SMD = −0.40, 95% CI [−0.72, −0.07], p = 0.02), fatigue (SMD = −0.52, 95% CI [−0.72, −0.31], p < 0.00001), and FCR (SMD = −0.51, 95% CI [−0.88, −0.14], p = 0.007). Furthermore, it significantly reduced perceived stress (SMD = −0.65, 95% CI [−1.11, −0.20], p = 0.005), lowered IL-6 levels (SMD = −0.30, 95% CI [−0.56, −0.03], p = 0.03), and improved overall quality of life (SMD = 0.67, 95% CI [0.39, 0.95], p < 0.00001). Sensitivity analyses indicated that the pooled effect sizes were stable.ConclusionMind–body exercises can effectively alleviate anxiety, depression, and fatigue in breast cancer patients, and appear beneficial in reducing FCR. Although pooled analyses also demonstrated statistically significant improvements in perceived stress, insomnia, quality of life, and IL-6 concentrations, the strength of the current evidence is limited, and the results should be interpreted with caution.Systematic review registrationThis systematic review was registered in PROSPERO under the registration number CRD42024568483. The registration details are available at: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024568483.